MANAJEMEN SUMBER DAYA MANUSIA DALAM MENDUKUNG TRANSFORMASI KOMPETENSI PELAYANAN RUMAH SAKIT UMUM DAERAH MELALUI SKEMA KERJASAMA PEMERINTAH DENGAN BADAN USAHA (KPBU): STUDI KASUS PADA SEBUAH RSUD TIPE B DI PROVINSI BALI - Wayan Hari Premananda (Nusantara Hasana Journal, 2026)
The implementation of hospital service transformation through the Public-Private Partnership (Kerja Sama Pemerintah dengan Badan Usaha/KPBU) scheme requires adequate human resource (HR) readiness as a key supporting factor in improving service competency. This study was conducted to describe the planning and management of HR required to support the transformation process of a type B Regional General Hospital (RSUD) located in Bali Province. The transformation is directed toward improving service competency from its current condition to an intermediate (madya) competency level, particularly in five priority service areas: Oncology, Cardiology, Neurology, Uronephrology, and Maternal and Child Health (referred to by the Indonesian acronym KJSUIA), as part of the implementation of a KPBU project. To maintain the confidentiality of the as-yet-unpublished feasibility study document, the hospital's identity and project-specific figures are not disclosed explicitly, but are instead presented in the form of general patterns rather than raw data. This study employs a descriptive qualitative approach using document study methods. The findings indicate that HR needs calculations for this type of transformation project are generally derived from three complementary approaches: fulfillment of targeted intermediate competency standards, workload analysis (analisis beban kerja/ABK) based on the Decree of the Minister of Health No. 21 of 2004, and optimal utilization of existing non-medical support staff. Additional findings show that the hospital's institutional status as a Regional Public Service Agency (Badan Layanan Umum Daerah/BLUD) tends to provide structural flexibility in HR governance, supported by a clearly defined organizational structure led by a Director and several Deputy Directors. Furthermore, a number of specialist and subspecialist physician competencies are generally not yet available or are still undergoing further education (fellowship) at the pre-feasibility study stage, indicating the need for structured recruitment, continued fellowship training support, and periodic evaluation to ensure the successful implementation of such transformation efforts.